Adaptation, awards culture, and the value of prestige - Kennedy-Karpat, Colleen ; Sandberg, Eric (Palgrave Macmillan, 2020)
This book explores the intersection between adaptation studies and what James F. English has called the “economy of prestige,” which includes formal prize culture as well as less tangible expressions such as canon formation, fandom, authorship, and performance. The chapters explore how prestige can affect many facets of the adaptation process, including selection, approach, and reception. The first section of this volume deals directly with cycles of influence involving prizes such as the Pulitzer, the Man Booker, and other major awards. The second section focuses on the juncture where adaptation, the canon, and awards culture meet, while the third considers alternative modes of locating and expressing prestige through adapted and adaptive intertexts. This book will be of interest to students and scholars of adaptation, cultural sociology, film, and literature.Machine generated contents note: |g1.|tAdaptation and Systems of Cultural Value /|rEric Sandberg -- |gpt. I |tAdapting Award Winners, Awarding Adaptations -- |g2.|tPulitzers Go to Hollywood /|rThomas Leitch -- |g3.|tBeware of Imitations: All about Eve (1950) /|rLaurence Raw -- |g4.|tHilary Mantel's Wolf Hall(s) and the Circulation of Cultural Prestige /|rEric Sandberg -- |g5.|tAdapting Queerness, Queering Adaptation: Fun Home on Broadway /|rJoanna Mansbridge -- |gpt. II |tAdaptation, Prestige, and the Canon -- |g6.|tOliver's Auteurs: The Cases of Lean and Polanski /|rJeffrey E. Jackson -- |g7.|tOrigins, Fidelity, and the Auteur: The Bengali Films of Tapan Sinha /|rPriyanjali Sen -- |g8.|tFortunes of Jane Austen as Chick Lit and Chick Flick /|rAnne-Marie Scholz -- |g9.|tJazz, Prestige, and Five Great Gatsby Film Adaptations /|rMichael Saffle -- |gpt. III |tLocating Prestige -- |g10.|tTrash Cinema and Oscar Gold: Quentin Tarantino, Intertextuality, and Industry Prestige /|rColleen Kennedy-Karpat -- |g11.|tHollywood Remake Massacre: Adaptation, Reception, and Value /|rLaura Mee -- |g12.|t"How do I act so well?" The British "Shakespearean" Actor and Cultural Cachet /|rAnna Blackwell.